PENGEMBANGAN COFA BUDAYA BETAWI DALAM MENINGKATKAN KEMAMPUAN MEMBACA DAN BERHITUNG ANAK USIA 5-6 TAHUN - Fatimah Fatimah; Nita; Hamid (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This study aims to examine the effectiveness of Congklak Fajar, a Betawi cultural-based learning media, in improving reading and numeracy skills of 5–6-year-old children at TK Fajar Semanan, West Jakarta. The background of this research arises from the fact that many children at this age still struggle with early reading skills, such as recognizing syllables, and with basic numeracy, such as performing simple addition. At the same time, the traditional game congklak, which is part of Betawi heritage, holds strong potential to be developed into an educational tool that is engaging, contextual, and aligned with children’s natural inclination to play. The study employed a quasi-experimental design with a pretest-posttest control group. Participants were divided into an experimental group, which learned using Congklak Fajar, and a control group, which used conventional learning methods. Research instruments included early reading and numeracy tests administered before and after treatment. Data were analyzed to determine the significance of improvements in literacy and numeracy skills across both groups. The results indicate that children in the experimental group showed significantly higher gains compared to the control group. The use of Congklak Fajar increased children’s motivation, engagement, and active participation during the learning process. These findings highlight that integrating local culture into learning media not only supports cultural preservation but also provides an effective and meaningful strategy to enhance the quality of early childhood education through enjoyable learning experiences.